The Relationship of Knowledge of The Covid and Prevention Protocol In Students of SDIT Al-Madinah To Compliance With The Covid and Prevention Protocol - Wuri Utami; Nurlaila, Nurlaila; Iswati, Ning (Journal Of Nursing Practice, 2021)
Background: The health problem that is currently in the spotlight and attention of the world is the Covid-19 disease. Covid-19 disease not only affects adults, but also affects children. The American Centers for Disease Control and Prevention (CDC) report shows that children and adolescents are more at risk for complications related to COVID-19. From the data collected from February to July 2020, it was found that 70% of the 121 cases of children and adolescents who died from diseases related to Covid-19 were aged 10-20 years.Purpose: This study aimed to determine the knowledge of the Covid 19 prevention protocol in SDIT Al students. Medina Against Compliance with Covid 19 prevention protocols.Methods: Quantitative research methods, correlational design, sample size 270 classes 4,5,6 at SDIT Al. Medina Kebumen. Quantitative research method, correlational design, sample size 270 grades 4,5,6 in SDIT Al. Medina Kebumen. Data analysis used statistical test with chi-square test.Results: The results showed that 131 respondents (70.8%) had good knowledge of the covid 19 prevention protocol for SDIT Al Madinah students, 168 respondents (90.8%) were obedient.Conclusion: Research analysis shows that there is a relationship between knowledge of the covid 19 prevention protocol in SDIT Al Madinah students and adherence to the covid 19 prevention protocol. (p = .000 <0.05)